Language, power, and program planning - E. Frances Rees (Adult Education Research Conference, 1996)
To explain the exercise of power through the use of language and its effects on power relations and program construction, the verbal interaction between three individuals in a program planing meeting was analyzed. Using critical language study, a type of discourse analysis, the investigation revealed that crucial planning action was situated by political relationships enacted through the use of language. Learning objectives, and adult education prescriptions and ethical imperatives took concrete shape within a socio-political context where the negotiation of power and interests was the central feature of "planing talk". e implications are that program construction is not only messy and contingent, but that it demands an awareness of many levels of meaning in discourse. Planners, therefore, must be prepared to use language skillfully and politically if they intend to act responsibly and exercise the full extent of their agency.